Mid-rapidity anti-baryon to baryon ratios in pp collisions at √s=0.9, 2.76 and 7 TeV measured by ALICE - Abbas, E.; Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agnello, M.; Agocs, A. G.; Agostinelli, A.; Ahammed, Z.; Ahmad, N.; et al. (SPRINGER, 2013)
The ratios of yields of anti-baryons to baryons probes the mechanisms of baryon-number transport. Results for (p) over bar /p, (Lambda) over bar/Lambda, (Xi) over bar (+)/(Xi) over bar (-) and (Omega) over bar (+)/(Omega) over bar (-) in pp collisions at root s = 0.9, 2.76 and 7 TeV, measured with the ALICE detector at the LHC, are reported. Within the experimental uncertainties and ranges covered by our measurement, these ratios are independent of rapidity, transverse momentum and multiplicity for all measured energies. The results are compared to expectations from event generators, such as PYTHIA and HIJING/B, that are used to model the particle production in pp collisions. The energy dependence of (p) over bar /p, (Lambda) over bar/(Lambda) over bar, (Xi) over bar (+)/(Xi) over bar (-) and (Omega) over bar (+)/(Omega) over bar (-), reaching values compatible with unity for root s = 7 TeV, complement the earlier (p) over bar /p measurement of ALICE. These dependencies can be described by exchanges with the Regge-trajectory intercept of alpha(J) approximate to 0.5, which are suppressed with increasing rapidity interval Delta y. Any significant contribution of an exchange not suppressed at large Delta y (reached at LHC energies) is disfavoured.
Keywords: PARTICLE-PRODUCTION; DIFFRACTION; LAMBDA; Physics